(untitled) (Research, Society and Development, 2024)
The aim of this review is to synthesize current knowledge about offensive and defensive transitions in football, highlighting how these critical moments impact performance indicators and styles of play. Transitions in football represent strategic instances, with profound strategic and strategic implications. This narrative review brings together the perspectives of different authors and analyzes the evolution of this field over time. With the support of real-time analysis tools, the work seeks to offer a comprehensive view of the dynamics of transitions in football. Counterattacks emerge as key outcomes often associated with transitions, corroborating the existing literature that points to the ability of these situations to provoke strategic responses from opposing teams. The review emphasizes the importance of an objective definition of the dichotomy between experimental and defensive transitions, considering the moment of play and the style of play, in order to avoid ambiguities and conceptual overlaps. Transitions are intrinsically complex, occurring regardless of ball possession, and their detailed understanding is essential to improve the performance of teams. By exploring the standings, determinants and impacts of transitions, this review contributes to a more in-depth and refined view of this crucial strategic component in football.